Immunomodulatory effects of recombinant BCG expressing MSP-1C of Plasmodium falciparum on LPS- or LPS+IFN-γ-stimulated J774A.1 cells - Mohamad, Dhaniah; Suppian, Rapeah; Mohd Nor, Norazmi (2014)
Macrophage phagocytosis is the first line of defense of the innate immune system against malaria parasite infection. This study evaluated the immunomodulatory effects of BCG and recombinant BCG (rBCG) strains expressing the C-terminus of the merozoite surface protein-1 (MSP-1C) of Plasmodium falciparum on mouse macrophage cell line J774A.1 in the presence or absence of lipopolysaccharide (LPS) or LPS + IFN-γ. The rBCG strain significantly enhanced phagocytic activity, production of tumor necrosis factor (TNF)-α, interleukin (IL)-1β, nitric oxide (NO), and inducible nitric oxide synthase (iNOS Mean + SE M (x107 CFU)”) as compared with parental BCG strain, and these activities increased in the presence of LPS and LPS+IFN-γ. Furthermore, the rBCG strain also significantly reduced the macrophage viability as well as the rBCG growth suggesting the involvement of macrophage apoptosis. Taken together, these data indicate that the rBCG strain has an immunomodulatory effect on macrophages, thus strengthen the rational use of rBCG to control malaria infection.